2018
DOI: 10.1002/aet2.10205
|View full text |Cite
|
Sign up to set email alerts
|

White Paper—Geriatric Emergency Medicine Education: Current State, Challenges, and Recommendations to Enhance the Emergency Care of Older Adults

Abstract: Older adults account for 25% of all emergency department (ED) patient encounters. One in five Americans will be 65 or older by 2030. In response to this need, geriatric emergency medicine (GEM) has developed into a robust area of academic and clinical interest, with extensive evidence-based research and guidelines, including clear undergraduate and postgraduate GEM competencies.Despite these developments, GEM content remains underrepresented in curricula and licensing examinations. The complex reasons for thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…44,[46][47][48] The number of studied geriatric education programs for ED physicians and nurses is surprisingly low, knowing that these professionals are often not well trained in geriatrics [19][20][21][22] and knowing that GEM expertise is needed to provide high-quality emergency care for the ever-increasing older patient population. 19,25 The programs that targeted ED physicians and nurses in this review were not assessed on their potential to improve clinical practice and health outcomes (Kirkpatrick level 4). Furthermore, they consisted of only one-time workshops or courses; spaced and repeated delivery of educational activities are needed to achieve long-term improvement of knowledge, skills, and change of practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44,[46][47][48] The number of studied geriatric education programs for ED physicians and nurses is surprisingly low, knowing that these professionals are often not well trained in geriatrics [19][20][21][22] and knowing that GEM expertise is needed to provide high-quality emergency care for the ever-increasing older patient population. 19,25 The programs that targeted ED physicians and nurses in this review were not assessed on their potential to improve clinical practice and health outcomes (Kirkpatrick level 4). Furthermore, they consisted of only one-time workshops or courses; spaced and repeated delivery of educational activities are needed to achieve long-term improvement of knowledge, skills, and change of practice.…”
Section: Discussionmentioning
confidence: 99%
“…15 Several studies have reported that ED professionals feel unconfident in dealing with complex older patients, [16][17][18] which may be related to the underrepresentation of older patient care issues in the medical and nursing curricula. 19 Surveys by the American College of Emergency Physicians (ACEP) found that practicing EPs considered it more difficult to manage older adults compared to younger counterparts and that the time spent during residency training on geriatric emergency medicine (GEM) was inadequate. 20 Furthermore, various reports have indicated that the majority of nurses caring for older populations have not received adequate geriatric education through formal or continuing programs.…”
mentioning
confidence: 99%
“…7,[11][12][13] The ED visit is an opportune time to initiate fall prevention measures because patients are optimally engaged, caregivers are often present, and hospital-based staff, such as pharmacists and physical therapists (PTs), are available. 14 However, EDs are busy environments, and ED clinicians lack the time and training 15 to perform fall risk assessments. A multidisciplinary team with expertise in fall prevention that evaluates these patients in the ED could address these limitations.…”
mentioning
confidence: 99%
“…Students benefited from geriatric specific education as well as practice working with interprofessional teams during the simulations. Geriatric education is particularly suited to simulation as a means to incorporate interprofessional interactions [ 15 ]. Students typically report enhanced realism and immediate feedback provided from standardized patients in medical simulation in comparison to more traditional methodologies [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The IOM suggests simulation be used in IPE to train novices and practitioners who would normally work together [ 14 ]. Team training using simulation is a proven method to teach both clinical and nonclinical skills [ 4 , 5 , 15 , 16 ]. Despite a wealth of knowledge supporting the benefits of IPE, many studies also highlight lessons learned with implementation [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%